PREVALENCE OF EQUINE HERPESVIRUSES (EHVS) INFECTION IN EGYPT: SYSTEMATIC META-ANALYSIS - Mohamed Marzok; Abdullah Al-mubarak; Magdy Elgioushy; Sabry El-khodery (Journal of Animal and Plant Sciences, 2025)
This report aimed to perform a meta-analysis on the occurrence of Equine herpesvirus (EHV) infection in Egypt. This systematic meta-analysis was performed in accordance with the PRISMA guidelines. Data were retrieved after a complete search, and eligible articles were identified. Data analysis with random-effects model was performed using a comprehensive meta-analysis software program. The results were presented as effect size, confidence intervals (CI), heterogeneity, and publication bias. A total of 1760 horses from 20 accepted studies were investigated for EHVs infection. Of these, 740 horses were found positive for EHVs, with a prevalence of 42%. The highest prevalence (100%) was during 2016 and 2020. EHV-1 was the most prevalent strain affecting horses in Egypt (p < 0.05). The prevalence of isolated strains was as follows: EHV-1 (492, 66.48 %), EHV-2 (151, 20.40 %), EHV-4 (105, 14.19 %), and EHV-5 (88, 11.89 %). The mixed EHV-1 and EHV-4 infections were predominant. However, the EHV-3 was not detected in any of these studies. At random effects, the Z-value was -1.539 (p-value = 0.124). The Q-value (373.103), I-squared (95.17), and p-value (0.000) were the final heterogeneity variables. The Egger’s linear regression test did not imply a publication bias, and its outcomes were intercept (-3.66), and 95% confidence interval (-8.23 to -0.9). The results of the present meta-analysis indicated a high prevalence of EHV infection in Egypt, particularly EHV-1. Therefore, more attention should be paid to the prevention and control of this disease.
Keywords: Horse; Epidemiology; EHV; Systematic review